Relationship Between Medication Adherence and Blood Pressure Control in Elderly Hypertensive Patients at the UPTD Bongo II Community Health Center (Puskesmas) - Nunung Djafar; Maulana Arif Murtadho (International Journal of Health, Economics, and Social Sciences (IJHESS), 2026)
Hypertension is one of the major health problems among the elderly and can lead to serious complications if not properly controlled. Medication adherence is an important factor in the management of hypertension. This study aimed to determine the relationship between medication adherence and blood pressure control among elderly patients with hypertension. This study employed an analytical design with a cross-sectional approach involving 60 respondents selected using a purposive sampling technique. Data were collected using a medication adherence questionnaire and blood pressure measurements and were analyzed using the Chi-Square test and Fisher’s Exact Test with a significance level of 0.05. The results showed that most respondents were non-adherent to medication (85.0%), and the majority had uncontrolled blood pressure (91.7%). Statistical analysis revealed no significant relationship between medication adherence and blood pressure control (p = 1.000). It can be concluded that medication adherence was not significantly associated with blood pressure control among elderly hypertensive patients. Therefore, increased education and a comprehensive approach are needed in managing hypertension among the elderly.